Democracy is at risk: beliefs of Chilean teachers about the transmission of hate speech in teacher education - Marolla-Gajardo, Jesús (Frontiers in Education, 2025)
Conversations about hate speech are a complex issue. It is not a new problem; on the contrary, society has been confronted with hate speech against specific communities at different moments. The present study aims to investigate the beliefs of Chilean teachers working in teacher education and their relationship with hate speech that may have occurred in their practice. The methodology was quantitative. The participants were 200 teachers. The data collection instrument was a survey to determine teachers’ beliefs. The results showed that teachers expressed concern about the problem and stated that action must be taken to combat hate speech. At the same time, they argued that their colleagues perpetuate and reproduce hate speech in their practice, which is also a complex situation that needs to be addressed. Finally, there is also a controversy about the limits of freedom of expression.